Sir Harold Nicolson and international relations the practitioner as theorist - Drinkwater, Derek (Oxford : Oxford University Press, 2005)
This is a study of the international thought of Sir Harold Nicolson (1886-1968), one of the most prominent commentators on diplomacy, international order, and world peace of his day, and an anti-appeasement MP.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nicolson, Harold, -- 1886-1968.; International relations